2016
DOI: 10.1038/ncomms13302
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-mediated codon-biased translation in mycobacterial hypoxic persistence

Abstract: Microbial pathogens adapt to the stress of infection by regulating transcription, translation and protein modification. We report that changes in gene expression in hypoxia-induced non-replicating persistence in mycobacteria—which models tuberculous granulomas—are partly determined by a mechanism of tRNA reprogramming and codon-biased translation. Mycobacterium bovis BCG responded to each stage of hypoxia and aerobic resuscitation by uniquely reprogramming 40 modified ribonucleosides in tRNA, which correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
207
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(219 citation statements)
references
References 58 publications
12
207
0
Order By: Relevance
“…As detailed in the next section, this type of secondary code information was first described for yeast, and was followed by additional examples involving separate wobble modifications and cognate groups of mRNAs. This was recently extended to Bacteria, in the Mycobacterium tuberculosis surrogate, Mycobacterium bovis during hypoxia-induced non-replicating persistence [107]. …”
Section: Targeting Sensitive Synonymous Codons For Cognate Specifmentioning
confidence: 99%
See 2 more Smart Citations
“…As detailed in the next section, this type of secondary code information was first described for yeast, and was followed by additional examples involving separate wobble modifications and cognate groups of mRNAs. This was recently extended to Bacteria, in the Mycobacterium tuberculosis surrogate, Mycobacterium bovis during hypoxia-induced non-replicating persistence [107]. …”
Section: Targeting Sensitive Synonymous Codons For Cognate Specifmentioning
confidence: 99%
“…During hypoxia-induced persistence, a phenomenon that occurs during tuberculosis granulomas formation, cmo 5 U modification of tRNA Thr UGU increases to aid translation of mRNAs enriched with the cognate codon [107]. …”
Section: Biased Codons Keyed To Trna Wobble Modification For Progmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of new roles for tRNA in cellular processes is greatly facilitated by the development of systems-levels approaches for assessing tRNA modification fluctuations in response to various stress and growth conditions, which was first utilized in yeast [41]. A more recent application of the systems-level approach by the same group revealed that a similar phenomenon occurs in Mycobacterium bovis BCG, which reprograms 40 modified nucleosides in response to hypoxia, consequently affecting translation of various genes involved in bacterial persistence [151]. A detailed investigation was conducted to understand the nearly 8-fold increase in cmo 5 U observed upon exposure to hypoxia, but this experiment also revealed a significant change in thionucleosides that has yet to be explored.…”
Section: Interconnectivity Between Trna Modification and Biosynthementioning
confidence: 99%
“…However, some regulatory mechanisms are not apparent from transcriptional results. For instance, the vaccine strain of Mtb, BCG, modifies 40 ribonucleosides in tRNA in response to hypoxia which results in the selective translation of mRNAs from families of codon-biased persistence genes [23]. Although Mtb exposed to nitric oxide stress respond rapidly at the transcriptome level, it takes some time of these changes to be revealed on protein level, a behavior that has been linked to protein degradation rather than proteins synthesis [24].…”
Section: Lessons From Genetic and Transcriptional Studies Of Mtbmentioning
confidence: 99%